Demystifying the Intricacies of Research Methodology, Scientific Publishing and Patenting - Balakumar, Pitchai; Sellappans, Renukha; Thangiah, Murugan; Shanmugam, Kumaran; Srividhya, P.K.; Jagadeesh, Gowraganahalli (Indian Journal of Pharmaceutical Education and Research, 2024)
It was generally believed that the most significant part of academic faculties’ work was teaching students, thus they devoted their all-time to the teaching-learning process. The basic requirements to become a faculty are more stringent now. At every stage of the academic profession, conducting prospective research and writing publications are regarded as essential tasks for a teaching faculty. One's scientific career can progress with a substantial body of research that is published. On 18 December 2023, the Office of Research and Development along with the Institution's Innovation Council of Periyar Maniammai Institute of Science and Technology (Deemed to be University), Thanjavur, India hosted an interactive one-day international symposium with the theme "Demystifying the intricacies of research methodology, scientific publishing and patenting." This symposium was intended for research scholars, teaching faculty, and students studying engineering, pharmacy, computer science, biomedicine, science, social science, and arts. Since 2004, our team has collaborated with several knowledgeable speakers to offer workshops, symposia and lectures on the aforementioned theme in various locations in India, at the request of scientific societies, colleges, and universities.1-5 Since postgraduates, doctoral students, and aspiring teacher-researchers are not systematically exposed to all of these practices, particularly in creating a research protocol and producing a high-caliber scientific paper for publication, this kind of routine training is crucial. We emphasize that before pursuing a career in research or academia, a person must have